2017
DOI: 10.1111/vec.12605
|View full text |Cite
|
Sign up to set email alerts
|

Status epilepticus in dogs and cats, part 1: etiopathogenesis, epidemiology, and diagnosis

Abstract: Status epilepticus is a medical emergency that can result in life-threatening complications involving the brain and systemic organs. Status epilepticus often requires comprehensive diagnostic testing, treatment with multiple anticonvulsant agents, and intensive supportive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 102 publications
(126 reference statements)
1
15
2
2
Order By: Relevance
“…In 1 report, 61.8% of dogs suffering from intracranial neoplasia developed seizures . In another report, 51% of dogs with intracranial neoplasia developed seizures, whereas other studies reported a seizure rate of 45% in dogs with intracranial neoplasia . All of the above‐mentioned studies found higher seizure activity rates than that observed in our study, but our study focused on short‐term seizure recurrence in dogs that already had experienced a seizure before consultation.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…In 1 report, 61.8% of dogs suffering from intracranial neoplasia developed seizures . In another report, 51% of dogs with intracranial neoplasia developed seizures, whereas other studies reported a seizure rate of 45% in dogs with intracranial neoplasia . All of the above‐mentioned studies found higher seizure activity rates than that observed in our study, but our study focused on short‐term seizure recurrence in dogs that already had experienced a seizure before consultation.…”
Section: Discussioncontrasting
confidence: 62%
“…8 In another report, 51% of dogs with intracranial neoplasia developed seizures, 9 whereas other studies reported a seizure rate of 45% in dogs with intracranial neoplasia. 29,35 All of the above-mentioned studies found higher seizure activity rates than that observed in our study, but our study focused on short-term seizure recurrence in dogs that already had experienced a seizure before consultation. Interestingly, another study found that seizure severity in more than half of the dogs with intracranial neoplasia progressed to cluster seizures by the time the dogs underwent MRI 8 partly explaining our finding that abnormal neurologic examination with predominance of prosencephalon signs is a risk factor for seizure recurrence.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations